Integrated System for Official Vehicles with Online Reservation and Moving Path Monitoring - Kuo-Tai Hsu; Wei-Chang Lu; Hao-Yu Jheng; Yun-Ting Hung; Xin-Zhang Chen; Wen-Ping Chen (Applied Sciences, 2022)
Companies have official vehicles for the convenience and time efficiency of employees to carry out official duties. However, private uses, false reports of fuel consumption, and excessive use by users may harm the company’s finance and reputation. Moreover, it is difficult to quantify and manage the use of official vehicles as they are used by different groups in the company. Locating vehicles also is a problem that is caused by inappropriate management. To solve these problems, an online monitoring and management system of official vehicles is proposed in this study. The system includes a set-top box (STB), key cabinet unit, line bot, and backstage management system in four major units with GPS and moving path tracking functions. The STB functions include GPS mobile tracking, power management, and Wi-Fi communication. The key cabinet unit manages key storage for the STB and detects the location of the set-top box. The backstage management system stores general information and GPS locations of vehicles. Line Bot allows online management, and the backstage management system provides administrators with information on official vehicle uses. The test result of the system shows successful monitoring of the vehicles on identifying moving paths, mileage, and locations with an accuracy of 5 m. The system prevents doubled reservations and informs the exact location of the vehicles. It helps the administrator of the official vehicles monitor and analyze the data of uses of the vehicles to improve the management efficiency and prevent misuse of the vehicles. The system also provides a solution for sharing economy of vehicles.